PENGEMBANGAN MODEL DISCOVERY LEARNING MELALUI WORKSHOP UNTUK MENINGKATKAN KOMPETENSI GURU MADRASAH TSANAWIYAH DI KECAMATAN BATEALIT KABUPATEN JEPARA - MUSTA’IN MUSTA’IN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to describe the process of developing a Discovery Learning Model through workshops, as well as to improve the competence of Madrasah Tsanawiyah teachers in Batealit District, Jepara Regency in compiling a Discovery Learning Model. The research was conducted in two cycles and each cycle consisted of four stages, namely: planning, implementation, observation and reflection. From the results of the analysis obtained information that there is an increase in the ability of Madrasah Tsanawiyah teachers in Kalinyamatan District, Jepara Regency in designing Discovery Learning Models. The improvement was shown (1) the ability of Madrasah Tsanawiyah teachers in Batealit District, Jepara Regency in designing discovery learning steps, from 17% in the first cycle to 100% in the second cycle; (2) the ability of Madrasah Tsanawiyah teachers in Batealit District, Jepara Regency in planning discovery learning, was formed from 17% in the first cycle to 100% in the second cycle; (3) the ability of Madrasah Tsanawiyah teachers in the district. Batealit Jepara Regency in carrying out discovery learning, from 33% in the first cycle to 100% in the second cycle; (4) the ability of Madrasah Tsanawiyah teachers in the district. Batealit Jepara Regency in making discovery learning hypotheses, from 33% in the first cycle to 100% in the second cycle; (5) Ability of Madrasah Tsanawiyah Teachers in Kec. Batealit Jepara Regency in making conclusions on discovery learning, from 27% in the first cycle to 100% in the second cycle. Other information shows that the response of Madrasah Tsanawiyah teachers in Batealit District, Jepara Regency in participating in the workshop process in designing the Discovery Learning Model 80% was very good and 20% responded well. This shows that Madrasah Tsanawiyah teachers in Batealit District, Jepara Regency really hope for a workshop to improve their competence. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan proses pengembangan Model Pembelajaran Penemuan (discovery learning) melalui workshop, serta meningkatkan kompetensi Guru Madrasah Tsanawiyah di Kecamatan Batealit Kabupaten Jepara dalam menyusun Model Pembelajaran Penemuan (discovery learning). Penelitian dilakukan dengan dua siklus dan masing-masing siklus terdiri atas empat tahapan, yakni: perencanaan, pelaksanaan, observasi dan refleksi. Dari hasil analisis diperoleh informasi bahwa terjadi peningkatan kemampuan Guru Madrasah Tsanawiyah di Kecamatan Kalinyamatan Kabupaten Jepara dalam merancang Model Pembelajaran Penemuan (discovery learning). Peningkatan itu ditunjukkan (1) kemampuan Guru Madrasah Tsanawiyah di Kecamatan Batealit Kabupaten Jepara dalam merancang langkah-langkah Pembelajaran Penemuan (discovery learning), dari 17% pada siklus I menjadi 100% pada siklus II; (2) kemampuan Guru Madrasah Tsanawiyah di Kecamatan Batealit Kabupaten Jepara dalam merencanakan Pembelajaran Penemuan (discovery learning) membentuk, dari 17% pada siklus I menjadi 100% pada siklus II; (3) kemampuan Guru Madrasah Tsanawiyah di Kec. Batealit Kabupaten Jepara dalam melaksanakan Pembelajaran Penemuan (discovery learning), dari 33% pada siklus I menjadi 100% pada siklus II; (4) kemampuan Guru Madrasah Tsanawiyah di Kec. Batealit Kabupaten Jepara dalam membuat hipotesis Pembelajaran Penemuan (discovery learning), dari 33% pada siklus I menjadi 100% pada siklus II; (5) Kemampuan Guru Madrasah Tsanawiyah di Kec. Batealit Kabupaten Jepara dalam membuat kesimpulan pada Pembelajaran Penemuan (discovery learning), dari 27% pada siklus I menjadi 100% pada siklus II. Informasi lain menunjukkan bahwa respon Guru Madrasah Tsanawiyah di Kecamatan Batealit Kabupaten Jepara dalam mengikuti proses workshop dalam rangka merancang Model Pembelajaran Penemuan 80% sangat baik dan 20% merespon baik. Ini menunjukkan bahwa Guru Madrasah Tsanawiyah di Kecamatan Batealit Kabupaten Jepara sangat mengharapkan adanya workshop dalam meningkatkan kompetensi mereka.